2015
DOI: 10.1002/pola.27749
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthesis of catechol‐functionalized poly(ethylene oxide) block and random copolymers

Abstract: Herein we develop a facile synthetic strategy for the functionalization of well‐defined polyether copolymers with control over the number and location of catechol groups. Previously, the functionalization of polyethylene oxide (PEO)‐based polymers with catechols has been limited to functionalization of the chain ends only, hampering the synthesis of adhesive and antifouling materials based on this platform. To address this challenge, we describe an efficient and high‐yielding route to catechol‐functionalized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…In the context of engineered biomaterials, cation-and aromaticrich sequences are prevalent in the adhesive proteins of several marine organisms, including mussels 17 , sandcastle worms 24 and barnacles 25 . Many researchers have sought to translate these protein sequences into synthetic, bioinspired adhesives by focusing predominantly on the role of the catecholic functional group 3,4-dihydroxyphenylalanine (Dopa) 17,[26][27][28][29][30] . However, these same studies 26,28,30 indicate that a reliance on Dopa alone is unrealistic for engineering an effective wet adhesion in underwater environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of engineered biomaterials, cation-and aromaticrich sequences are prevalent in the adhesive proteins of several marine organisms, including mussels 17 , sandcastle worms 24 and barnacles 25 . Many researchers have sought to translate these protein sequences into synthetic, bioinspired adhesives by focusing predominantly on the role of the catecholic functional group 3,4-dihydroxyphenylalanine (Dopa) 17,[26][27][28][29][30] . However, these same studies 26,28,30 indicate that a reliance on Dopa alone is unrealistic for engineering an effective wet adhesion in underwater environments.…”
mentioning
confidence: 99%
“…Many researchers have sought to translate these protein sequences into synthetic, bioinspired adhesives by focusing predominantly on the role of the catecholic functional group 3,4-dihydroxyphenylalanine (Dopa) 17,[26][27][28][29][30] . However, these same studies 26,28,30 indicate that a reliance on Dopa alone is unrealistic for engineering an effective wet adhesion in underwater environments. Further, Dopa is conspicuously sparing or non-existent in the highly adhesive proteins of some marine organisms, such as green mussels 8 and barnacles 25 , whereas Dopa is prevalent in non-adhesive proteins, such as the plaque-coating proteins of some marine mussels 17 .…”
mentioning
confidence: 99%
“…Menyo et al in 2013, who used carboxylic‐acid‐functional 4‐arm poly(ethylene glycol) (PEG) and a surplus of catechol to produce end‐functionalized dopa‐functional PEG; and by Xu et al in 2012, who functionalized poly(pentafluorophenyl acrylate) with dopamine to modify titanium surfaces . In 2015, Mattson et al furthermore showed that a co‐polymer of ethylene oxide and allyl glycidyl ether (P(EO‐ co ‐AGE)) could successfully be functionalized with dopa‐groups using thiol‐ene coupling (TEC) chemistry . Though effective and highly controlled, this approach required protection of the catechol before functionalization, resulting in a multistep synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…that a co-polymer of ethylene oxide and allyl glycidyl ether (P(EO-co-AGE)) could successfully be functionalized with dopa-groups using thiol-ene coupling (TEC) chemistry. 23 Though effective and highly controlled, this approach required protection of the catechol before functionalization, resulting in a multistep synthesis. The versatility and specific character of TEC, 24 however, promote TEC as a promising chemistry for the synthesis of various dopa-functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…To build PGs with various architectures and versatile functionality, many functional epoxide monomers have been developed, including ethoxyethyl glycidyl ether (EEGE), ethoxy vinyl glycidyl ether, allyl glycidyl ether (AGE), N , N ‐diisopropyl ethanolamine glycidyl ether, N , N ‐dibenzyl amino glycidol, and glycidyl propargyl ether (GPE) . These monomers are often copolymerized with glycidol to produce PGs with diverse structures.…”
Section: Introductionmentioning
confidence: 99%